2013
DOI: 10.1002/ange.201300881
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)‐Catalyzed Redox‐Neutral Coupling of N‐Phenoxyacetamides and Alkynes with Tunable Selectivity

Abstract: Selektiver Feinschliff: Eine neuartige oxidierende dirigierende Gruppe wurde für die Rhodium(III)‐katalysierte C‐H‐Funktionalisierung von N‐Phenoxyacetamiden mit Alkinen entwickelt. Durch geringfügige Veränderung der Reaktionsbedingungen lassen sich entweder ortho‐Hydroxyphenyl‐substituierte Enamide oder Benzofurane mit hoher Selektivität erhalten (siehe Schema; Cp*=C5Me5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(18 citation statements)
references
References 64 publications
0
17
0
1
Order By: Relevance
“…Since these pioneering studies, chelation-assisted alkyne hydroarylation has been explored with various transition-metal catalysts and a wide range of heteroatom-based directing groups 4,6,[17][18][19][20] . However, removal of these ortho-directing groups from the hydroarylation products requires additional chemical transformations and is not always achievable [21][22][23] . Thus, access to ortho-substituted alkenylarenes by alkyne hydroarylation is limited by the nature of the ortho-directing groups, and access to meta-or para-substituted alkenylarenes has not been achieved selectively by existing methods for alkyne hydroarylation 24,25 .…”
mentioning
confidence: 99%
“…Since these pioneering studies, chelation-assisted alkyne hydroarylation has been explored with various transition-metal catalysts and a wide range of heteroatom-based directing groups 4,6,[17][18][19][20] . However, removal of these ortho-directing groups from the hydroarylation products requires additional chemical transformations and is not always achievable [21][22][23] . Thus, access to ortho-substituted alkenylarenes by alkyne hydroarylation is limited by the nature of the ortho-directing groups, and access to meta-or para-substituted alkenylarenes has not been achieved selectively by existing methods for alkyne hydroarylation 24,25 .…”
mentioning
confidence: 99%
“…We embarked on our design by investigating a reaction between N-phenoxyacetamide (1a) and diphenylacetylene (2a), which was recently published by Lu and co-workers to undergo a classic point-to-point ortho-selective vinylation reaction and yield the enamide product (3aa) 11 . Treatment of 3aa with various transition metals in an attempt to cyclize the oxyacetamide onto the double bond quickly identified that using 1.2 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…1a). 7 Strategies trying to address this drawback include incorporation of the DG into a heterocycle via in situ condensation reactions or development of a traceless DG [8][9][10][11][12][13][14][15][16] . For example, we have developed a fully cleavable DG that allowed both convenient removal and conversion to various functional groups after the C-H activation step.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Recently,t he redox-neutrals trategye mploying an oxidizing directing group [9] hasb eene merged in the field of C-H functionalization. [11,12] We envisioned that this powerful strategyc ould be explored for the synthesiso fu nsymmetrical ortho-biphenols. [10] In our own efforts, [11] we developed atraceless oxidizing directing group ONHAcf or the redox-neutral C-Hf unctionalization of ArONHAct owards an efficient synthesis of ortho-functionalizedp henols (Scheme 1a).…”
mentioning
confidence: 99%